2006
DOI: 10.1027/0227-5910.27.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Media Guidelines on the Reporting of Suicide

Abstract: There is strong evidence for the existence of the Werther effect, or the phenomenon of an observer copying suicidal behavior he or she has seen modelled in the media. As a consequence, a number of countries have developed guidelines that promote responsible reporting of suicide. Using nine such guidelines as examples, this paper demonstrates that they tend to have similar content (emphasizing, for example, that suicide should not be glamorized or sensationalized and that explicit descriptions should be avoided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 10 publications
(9 reference statements)
3
169
0
7
Order By: Relevance
“…This review also found substantially more imitative effects for female suicide rates than male rates, and less likelihood of imitative effects in younger or middle aged groups. The association between media reporting and suicide is also dependent on the length of time between the occurrence of the suicide and publishing of the story, the number of media sources covering the event, and the specific characteristics of case (Pirkis et al, 2006). Recent research by Niederkrotenthaler and colleagues (2010) reports that printed media articles that focused on specific suicide deaths and "myths" of suicide had a detrimental effect, while those articles on coping behaviours and suicide ideation (not accompanied by suicidal behaviours) were not associated with an increase in suicide.…”
Section: Media Reporting Of Suicide (N = 19)mentioning
confidence: 99%
See 1 more Smart Citation
“…This review also found substantially more imitative effects for female suicide rates than male rates, and less likelihood of imitative effects in younger or middle aged groups. The association between media reporting and suicide is also dependent on the length of time between the occurrence of the suicide and publishing of the story, the number of media sources covering the event, and the specific characteristics of case (Pirkis et al, 2006). Recent research by Niederkrotenthaler and colleagues (2010) reports that printed media articles that focused on specific suicide deaths and "myths" of suicide had a detrimental effect, while those articles on coping behaviours and suicide ideation (not accompanied by suicidal behaviours) were not associated with an increase in suicide.…”
Section: Media Reporting Of Suicide (N = 19)mentioning
confidence: 99%
“…Media guidelines for the reporting of suicide are commonly included in national intervention efforts because of the concern that insensitive descriptions may result in an increase in suicide deaths (Cheng, Hawton, Lee, & Chen, 2007;Fu & Yip, 2007;Pirkis, Blood, Beautrais, Burgess, & Skehans, 2006;Stack, A. MILNER ET AL. 2009). There is some evidence to support this perspective, as recent research papers identify an increase in suicide rates after damaging media reports (Chen et al, 2010;Chen, Chen, & Yip, 2011;Fu, Chan, & Yip, 2011;Gould, 2001;Hagihara, Tarumi, & Abe, 2007;Niederkrotenthaler & Sonneck, 2007;Pirkis & Blood, 2001aStack, 2005;Sudak & Sudak, 2005;Tsai & Cho, 2011).…”
Section: Media Reporting Of Suicide (N = 19)mentioning
confidence: 99%
“…[22][23][24] Worldwide, numerous guidelines have been developed to advise the media on best practices. ABSTRACT BACKGROUND: Exposure to media reporting on suicide can lead to suicide contagion and, in some circumstances, may also lead to help-seeking behaviour.…”
mentioning
confidence: 99%
“…In acknowledgement of these issues, media reporting guidelines with similar content have been developed around the world, including in Canada. 10,11 Evidence suggests that media reports often focus on immediate factors involved in suicide death and omit mention of important underlying treatable causes, such as mental disorders or substance misuse. 7 This emphasis belies the complexity of the issues that contribute to suicide death.…”
Section: Perspectives Of Mental Health and Suicide Prevention Expertsmentioning
confidence: 99%